Axiological survey of the modern cultural-educational practices of personality: [monograph] - Molodychenko, V. V.; Oleksenko, Roman; Олексенко, Роман Іванович; Олексенко, Роман Иванович; Troitska, T. S.; Fedorova, O. V.; Taranenko, Halyna; Тараненко, Галина Григорівна; Тараненко, Галина Григорьевна (Melitopol : Melitopol Bohdan Khmelnytsky State Pedagogical University Press, 2016)
The monograph is devoted to the hardly explored topic that reveals methodological, theoretical and praxeological potential of modern culturaleducational practices of personality as a unity of diversity and continuum of methods of human’s existence, synthesis of its life practices, in particular economic, religious, political and etc. The authors updated the role of education, science, cultural-educational practices in common to mankind sense in modernization of cultural-spiritual life. The monograph can be used by scholars, postgraduate students and students. The majority of the problems that are highlighted in the monograph have discursive and discussion character and incite to competent dialogue between all people that are interested in these questions.
Keywords: modern education; axiologization; religious socialization